Marker profile of digestive system organs comorbid pathology in children - Sokolnyk, Snizhana Vasylivna; Sorokman, Tamila Vasylivna; Bodnar, Ganna Borysivna; Moldovan, Pavlo Mykhailovych; Loziuk, Iryna Yaroslavivna; Vaskul, Nadiia Yaroslavivna (Journal of Education, Health and Sport, 2020)
The article highlights the current state of the comorbid pathology of the digestive system problem in children. Attention is paid to the most significant trigger factors of comorbid pathology of the digestive system organs in children and they are given a prognostic assessment with the development of a mathematical model of developmental risk. Aim. To identify predictors of comorbid pathology of the digestive system in children and to determine their prognostic value. Material and methods. 115 children with comorbid pathology of the digestive system organs and 80 healthy children aged 7-18 years were examined. The state of biological, social and genealogical well-being was determined by means of questionnaires. Laboratory and instrumental studies were conducted in accordance to the Ministry of Health ofUkraineorders in the specialty "Pediatric Gastroenterology" with the informed consent of patients to participate in the study. Results. Etiologically determining risk factors for the development of comorbid pathology of the digestive system organs in children are unfavorable genealogical history with hereditary burden by both pedigrees, age and sex of the child, H. pylori infection, stress, vitamin D3 and iodine deficiency, endothelial dysfunction, disruptions of regional blood flow in the abdominal trunk, premorbid background. Conclusion. It is established that the risk of comorbid pathology of the digestive system in children will increase by 4.27 times if the child has identified by us non-modifying factors, and by 2.62 times under the influence of modifying factors.